Evaluating distributed cognition. - Green, Adam (Synthese, 2014)
Human beings are promiscuously social creatures, and contemporary epistemologists are increasingly becoming aware that this shapes the ways in which humans process information. This awareness has tended to restrict itself, however, to testimony amongst isolated dyads. As scientific practice ably illustrates, information-processing can be spread over a vast social network. In this essay, a credit theory of knowledge is adapted to account for the normative features of strongly distributed cognition. A typical credit theory analyzes knowledge as an instance of obtaining success because of or through the ability of the individual knower. The extended credit theory developed here broadens this framework so as to accommodate team-like epistemic achievements. The extended credit theory is then contrasted with some similar proposals given from within a process reliabilist framework. Once one isolates pairs of cases of distributed cognition in which there is a difference between sheer reliability and reliability grounded in ability, one can see that the extended credit theory maps the normative terrain better than the alternatives.